Mixing and mastering in the box: The guide to making great mixes & final masters on your computer - Savage, Peter (Oxford Oxford university press, 2014)
Describes the fundamentals of setting up a complete mixing and mastering environmentProvides the essentials on mixing and mastering gearOffers detailed and practical instructions on how to develop the skill set needed for mixingGives important tips on honing the specialized listening skills behind final mastersReveals the secrets of collaborating with professional musicians on mixes and masters